HADITH STUDIES FROM THE SHIA PERSPECTIVE: Characteristics, Validity, and Literature of Shia Hadith - Saputri, Gefi Melyana; Jatmiko, Mokhammad Priyo; Lyatin, Uul (RIWAYAH, 2023)
Shiites are part of the Muslim community and have many differences with Muslims in general in several aspects, such as the concept of faith, the practice of Quranic verses, fiqh, and hadith. Shia has its own scientific concept in relation to hadith. This article examines the hadith discourse from the Shiite perspective. This research was conducted to find out the characteristics of Shia hadith, the validity of Shia hadith, and the literature of Shia hadith, namely al-Kafi by Imam al-Kulaini. The study of library research data was collected from literature in the form of books, articles, journals, and various other literature related to the Shiite community, especially regarding the Shiite hadith: The characteristics of Hadith in the Shiite tradition are in the form of everything attributed to the twelve Imams, who are believed to be ma’shum, in the form of words, deeds, and decrees. The validity of Hadith among the Shiites comes from all the sayings of the infallible Imams of Ahlul Bayt, which are equal to the words of the Prophet Muhammad and must be followed. The Shia hadith literature Al Kafi has always ranked first in the order of hadith books among the Imamiah Shia.[Kaum Syi’ah merupakan bagian dari masyarakat Islam dan mempunyai banyak perbedaan dengan umat Islam pada umumnya dalam beberapa aspek, seperti konsep keimanan, pengamalan ayat-ayat Alquran, fiqh, dan hadis. Syiah mempunyai konsep keilmuan tersendiri dalam kaitannya dengan hadis. Artikel ini mengkaji wacana hadis dari sudut pandang Syiah. Penelitian ini dilakukan untuk mengetahui ciri-ciri hadits Syiah, kesahihan hadits Syiah, dan literatur hadits Syiah yaitu al-Kafi karya Imam al-Kulaini. Kajian data penelitian kepustakaan dikumpulkan dari literatur berupa buku, artikel, jurnal, dan berbagai literatur lain yang berhubungan dengan masyarakat Syi’ah khususnya mengenai hadis Syi’ah: Ciri-ciri Hadis dalam tradisi Syi’ah berupa segala sesuatu dikaitkan dengan kedua belas Imam yang diyakini ma’shum, baik berupa perkataan, perbuatan, maupun ketetapan. Keabsahan Hadis di kalangan Syi’ah berasal dari seluruh sabda Imam Maksum Ahlul Bayt yang sama dengan sabda Nabi Muhammad SAW dan wajib diikuti. Literatur hadis Syiah Al Kafi selalu menduduki peringkat pertama dalam urutan kitab hadis di kalangan Imamiah Syiah.]